KURIKULUM MERDEKA DAN KURIKULUM BERBASIS CINTA TERHADAP PEMBENTUKAN MURID UNGGUL DI MIS MUHAMMADIYAH 3 AL-FURQAN - Inayah, Fahrina; Hikmah; Nurmadina, Azkya; Syifa Agna Nuzila, Lara; Mahfuzhah, Laily; Aslamiah; Ayu Pratiwi, Diani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of an appropriate curriculum is an important factor in developing outstanding students in both academic and character aspects. This study aims to describe the implementation of the Merdeka Curriculum and Love-Based Curriculum (KBC) in shaping outstanding students at MIS Muhammadiyah 3 Al-Furqan. This research used a qualitative approach with observation, interviews, documentation, and literature review as data collection techniques. The research participants consisted of the principal and the vice principal for curriculum affairs. The findings show that the implementation of the Merdeka Curriculum and KBC was carried out through character strengthening, student-centered learning, teacher professional development, and the habituation of religious and social values. The school also provides opportunities for students to develop their academic and non-academic potential according to their interests and talents. Therefore, the implementation of both curricula contributes positively to producing outstanding, character-driven, and high-achieving students.